Skin to skin contact for very low birthweight infants and their mothers. Issue 11 (November 1988) - Whitelaw, A; Heisterkamp, G; Sleath, K; Acolet, D; Richards, M
Abstract : Separation between mothers and very low birthweight infants is often prolonged with subsequent psychological distress, behaviour problems, and lactation failure. Babies as small as 700 g, who no longer require oxygen, can be safely and enjoyably held naked, except for a nappy, between the mother's breasts for up to four hours a day. We have carried out a randomised trial among babies less than 1500 g. Seventy one infants were randomised. In 35, the mother was helped to hold her baby in skin to skin contact and encouraged to do so whenever she visited the baby. In 36, the mother was encouraged to handle her baby but without skin to skin contact. Mothers using skin to skin contact lactated for four weeks longer on average than the control group. At 6 months of age the infants who had skin to skin contact cried significantly less than the control group. Skin to skin contact can safely and enjoyably be offered to very low birthweight infants especially in developing countries where the mother's lactation is vital.